El ‘problema indígena’ y la construcción de la nación en Bolivia y Ecuador durante el siglo XIX: la perspectiva de las luchas por la hegemonía - Rodríguez, Edwin Cruz (Diálogos Latinoamericanos, 2012)
This document analyses the Building-Nation hegemonic projects carried out in Bolivia and Ecuador in the Nineteenth Century, and it also wrangles the idea that indigenous people were excluded from their already formed ‘nations’ to show the ways these groups were articulated to the independence Creole Nation project, as well as for the Liberals Nation-formation project in the second half of the XIX century. It also addresses the ways in which the Indians attempted to participate in their nationsbuilding project. Both Nation-building projects articulated indigenous groups passively. The Creole national project intended to integrate them through turning these indigenous groups into ‘citizens’ but just giving this merely status, while the Liberal Project aimed to ‘civilize’ banishing their communal life social practices and depriving them from their landholding. One of the arguments in this article is the one that states Indians were not passive agents and they deployed collective actions, from violent uprisings to access to justice, and demanded an active place in the process of nation building.